The Assessment Practices of Primary School Teachers of French Foreign Language: The Case of Costa Rica: Las prácticas evaluativas de docentes de primaria de francés como lengua extranjera: el caso de Costa Rica (2022)
Introduction: Research on assessment practices in language has been a topic that has aroused a lot of interest in recent years. Therefore, this research aims, on the one hand, to characterize the conceptions of the assessment of French teachers as a foreign language and, on the other hand, to analyse their assessment practices. Methodology: Based on these objectives, exploratory research is carried out in which 26 primary school teachers participated through an online questionnaire. Results and discussion: As main results, it was found that the teachers conceive assessment such as verification and knowledge verification. Their assessment practices are often framed in traditional assessment and they are influenced by what is established by the Ministry of Public Education. That is why the teacher is generally the person responsible for the entire assessment process and the correction. Conclusions: Finally, the assessment practices are influenced by the teachers’ beliefs and by the institutional context that they play a primary role in the assessment process.